Humanities and Social Sciences at a Crossroads? The Bibliographic/Bibliometric Divide - Žic Fuchs, Milena (Array, 2012)
This invited speech dealt with issues of bibliographic/bibliometric attempts at evaluating Humanities and Social Sciences research. Especially stressed was the issue of making SSH research visible, with special reference to outputs in national languages and outputs in monographs, book chapters, etc. that is, typical ways in which SSH scholars publish their research.